Regional income convergence in turkey: an empirical analysis from an endogenous growth perspective - BOLKOL, HAKKI KUTAY (My University, 2023)
This study analyzes convergence among regions of Turkey from an endogenous growth perspective. The results show that human capital, which is represented with R&D personnel, has a negative impact on economic growth in the regions based on its percentage in total employment. Moreover, we find that there is an estimated U-shaped relationship, which implies that if the percentage of R&D personnel in total employment increases after a certain level, the effect has a tendency of turning positive; the west region is especially closer to having a positive effect. However, regarding convergence, the relatively high-income west is closer to experiencing the positive effect of R&D personnel. Moreover, due to the relatively low percentage of R&D personnel in the east region, the economic growth of the east region is more negatively affected by R&D personnel. Therefore, using a strategy that is based on increasing the percentage of R&D personnel cannot help the east region to close the differences in income.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Kalkınma İktisadı ve İktisadi Büyüme; Social Sciences and Humanities; Economics; Development Economics and Economic Growth; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities